The Augmentation of a Flight Control Mechanism for a Hybrid Fixed-Wing VTOL Drone for Parcel Delivery - Mohd Shakir See, Mohamad Nadjmi; Zulkafli, Mohd Fadhli; Pairan, Muhammad Fahmi; Chakraverty, Seyhrvin Kumar; Mahmud, Izzat Khair (Progress in Aerospace and Aviation Technology, 2022)
Several companies are experimenting with multicopters drones to deliver packages to customers. Although they are less aerodynamically efficient than fixed-wing aircraft, their ability to do the vertical take-off and landing (VTOL) makes them ideal for delivery services. In this study, two methodologies will be used to build the drone which is software simulation and experimental approach. Software such as SIMNET is used to simulate and design an electronic operation of the drone while Mission Planner is used to setup the flight controller. Electronics layout is done prior to ensure a clear sight of work, components and information through the software. The flight controller used is called Pixhawk which is an open hardware mainly used for drone. The radio control system is also setup to be used as the link to control the flight controller. Flight tests were also performed to study the behavior of the UAV at various percentage of throttle. At 60 percent throttle, the drone yaws continously to the left at 63.43 degrees at 4.879 degrees per second during test flights. With a payload weight of 516g, it tilted to the front nose down, with support provided at the tip of the left wing. With more design and calibration advancements, experimental findings that are similar to theoretical outcomes might be attained. Flight data after each test flight is extracted from the software and analysed for further improvement. The fabrication of complete prototype could not be finished within the stipulated time due to a delay in acquiring new parts such as propeller due to a problem, as well as procuring the appropriate material for the wing. A test of the drone motions including roll, pitch, and yaw, is also carried out using flight charts to validate the suggested design parameter. The drone tends to fly better with the motor turning with the same orientation rather than turning with different orientation due to better stability. This flight chart allows users to choose the best design parameters by determining the length of the wingspan, motor RPM, and propeller diameter that are expected to meet the performance requirements in these three flying motions. The procedure for estimating the UAV's battery usage has also been presented in the flight chart.